Constructing the national figure: visual and narrative approaches to the Revival (Research Announcements "Heritage BG", 2025)
The article aims to examine how the television series The Revival of the Third Bulgarian State, part of the program The Altars of Bulgaria, constructs the images of Bulgarian National Revival heroes (Paisii of Hilendar, Neofit Rilski, Petar Beron, Georgi Rakovski, Rayna Knyaginya, Zahari Zografski and others) as emblems of national identity. The visual and narrative approach of the program combines pathos-laden metaphors and traditional narratives with attempts at a critical interpretation of the Bulgarian Revival. The analysis shows how these images are presented ambivalently, navigating between established historical clichés and the need for a more contemporary, scholarly reading. Thus, on the one hand, the classical patriotic and educational rhetoric is preserved, while on the other, new relativist and critical interpretations are introduced, enabling a more complex rethinking of the heroic figures and events.
Keywords: national identity; Bulgarian Revival heroes; media representation; critical interpretations; Narrative approaches